Large Deformation Disaster Mechanism and Control Technique for Deep Roadway in Faulted Zone - Liu, Xuewei; Chen, Juxiang; Liu, Bin; Luo, Yong; Zhu, Yuanguang; Huang, Xing (Frontiers in Earth Science, 2022)
In order to study mechanism and control technique of deep roadway in faulted zone, the 11-2 transport roadway of Guqiao coal mine in Huainan was taken as a case. The research roadway encountered two faults named F97 and F98 and suffered a severe large deformation disaster (including floor heaving, side cracking, steel arch bending, and section shrinkage) after excavation. Then, laboratory tests, in-situ stress measurement, and numerical simulation results indicate that lower strength and easy to be soften of surrounding rock is immanent cause, while high geo-stress is external inducement of large deformation. The continuous behaviors of opening, moving, and rotation of rock blocks under the above factors finally caused large deformation disaster. Finally, a control technique named stages and combination control method (SCCM) has been proposed. This technique contains two steps namely primary (including prestressed anchor bolt, shotcrete, and grouting) and secondary (including prestressed cable) support stages. Numerical calculation and in-situ monitoring results indicate that the SCCM technique can stop the failure of surrounding rock and control displacement of surrounding rock effectively.